Concepts of Puta and its usage - Herapathdeniya, S.K.M.K.; Samarakoon, S.M.S. (Graduate Studies Division, University of Kelaniya, 2014)
Rasashastra is a branch of Ayurveda pharmaceuticals speacially dealing with the minerals, metals ...
Keywords: Puta; Bhasma; Shodana; Marana; Amritikarana